B lymphocyte inhibition of anti-tumor response depends on expansion of Treg but is independent of B-cell IL-10 secretion - Zhang, Yu; Eliav, Yair; Shin, Seung-uon; Schreiber, Taylor H.; Podack, Eckhard R.; Tadmor, Tamar; Rosenblatt, Joseph D. (Cancer Immunology, Immunotherapy, 2013)
The mechanisms by which B lymphocytes inhibit anti-tumor immunity remain poorly understood. Murine EMT-6 mammary tumors grow readily in immune competent mice (BALB/c), but poorly in B-cell-deficient μ −/− BALB/c mice (BCDM). T regulatory cell (Treg) expansion and function were impaired in BCDM compared with BALB/c. In this study, we compared tumor growth, Treg cell proliferation, tumor lymphocyte infiltration and cytolytic T cell activity in BALB/c, BCDM and BCDM partially reconstituted with B cells by adoptive transfer (BCDM+B). Partial reconstitution of BCDM with adoptively transferred B cells restored EMT-6 tumor growth, which was independent of IL-10 secretion by B cells. Instead, high frequencies of intratumoral B cells were associated with increased recruitment and proliferation of Treg cells within the tumor microenvironment. The B-cell-dependent accumulation of Treg within the tumor microenvironment was associated with reduced tumor infiltration by CD49+ NK and CD8+ T cells and reduced cytotoxic T cell activity against EMT-6 targets. Our studies indicate that tumor-dependent immunosuppression of T-cell-mediated anti-tumor immunity is coordinated within the tumor microenvironment by B-cell-dependent cross talk with Treg cells, which does not require production of IL-10 by B cells.